Continuous Inventory of our Forest Resources - Agrawala, N. K. (Indian Forester, 1986)
Sound adequate data base has been a major constraint in the forestry planning processs in India. Forest inventory is necessary for the periodic assessment of the forest resources as well as the land on which the forest resources are situated. The paper deals with the advantage of continuous inventory of Forest resources, over the Pre-investment inventory. The author describes the design of National forest inventory and application of aerial photointerpletation in forest inventory.